Incidence of cutaneous melanoma and Merkel cell carcinoma in patients with primary cutaneous B-cell lymphomas: A population study of the SEER registry - Banner, Lauren; Joffe, Daniel; Lee, Emily; Porcu, Pierluigi; Nikbakht, Neda (Frontiers in Medicine, 2023)
The increased incidence of cutaneous melanoma (CM) development in patients with hematologic malignancies (HM) is well established. While the risk of CM has been assessed in some subtypes of HM, the CM incidence in primary cutaneous B-cell lymphoma (PCBCL) has not been interrogated. In our cutaneous lymphoma tertiary referral center, CM was observed occurring at a higher-than-expected incidence rate in our PCBCL patients. There were 6 cases of CM in 37 PCBCL clinic patients with an incidence of 16.21% (95% CI: 7.65-31.1) which was increased compared to the incidence in the general population of 0.022% (95% CI, 0.068, 0.327). We retrospectively analyzed the standardized incidence ratios (SIR) in a population-level Surveillance, Epidemiology and End Results (SEER) cohort of 5,321 PCBCL patients. There were 38 cases of CM in PCBCL SEER cohort patients (SIR, 1.37; 95% CI, 0.97-1.88). In the SEER cohort, we found that factors associated with development of CM in PCBCL patients were male gender, age over 50 years old at CM diagnosis, latency1-5 years after diagnosis of PCBCL and subtype of PCBCL being primary cutaneous follicle center lymphoma (PCFCL). Males aged 50-54 with PCFCL had a significantly increased risk of CM development (SIR, 8.31; 95% CI, 1.01-30.03). Although PCBCL is generally indolent, patients, especially middle-aged to older males should undergo annual screening for CM in the first five years after diagnosis of PCBCL.